Albuminuria as a risk factor for mild cognitive impairment and dementia—what is the evidence?. (5th November 2021) - Bikbov, Boris; Soler, Maria José; Pešić, Vesna; Capasso, Giovambattista; Unwin, Robert; Endres, Matthias; Remuzzi, Giuseppe; Perico, Norberto; Gansevoort, Ron; Mattace-Raso, Francesco; Bruchfeld, Annette; Figurek, Andreja; et al.
ABSTRACT: Kidney dysfunction can profoundly influence many organ systems, and recent evidence suggests a potential role for increased albuminuria in the development of mild cognitive impairment (MCI) or dementia. Epidemiological studies conducted in different populations have demonstrated that the presence of increased albuminuria is associated with a higher relative risk of MCI or dementia both in cross-sectional analyses and in studies with long-term follow-up. The underlying pathophysiological mechanisms of albuminuria's effect are as yet insufficiently studied, with several important knowledge gaps still present in a complex relationship with other MCI and dementia risk factors. Both the kidney and the brain have microvascular similarities that make them sensitive to endothelial dysfunction involving different mechanisms, including oxidative stress and inflammation. The exact substrate of MCI and dementia is still under investigation, however available experimental data indicate that elevated albuminuria and low glomerular filtration rate are associated with significant neuroanatomical declines in hippocampal function and grey matter volume. Thus, albuminuria may be critical in the development of cognitive impairment and its progression to dementia. In this review, we summarize the available evidence on albuminuria's link to MCI and dementia, point to existing gaps in our knowledge and suggest actions to overcome them. The major question of whether interventions that target increased albuminuria could prevent cognitive decline remains unanswered. Our recommendations for future research are aimed at helping to plan clinical trials and to solve the complex conundrum outlined in this review, with the ultimate goal of improving the lives of patients with chronic kidney disease. Graphical Abstract: